A phonemic check list for Kannada articulation tests - PJ, Kumar; N, Rathna; PD, Manohar (Journal of All India Institute of Speech and Hearing)
Tests of Articulation in the Kannada language was developed in 1972 (Ram Mohan Babu, Rathna and Bettageri, 1972). The tests consist of two parts.